Inter-temporal discounting and uniform impatience - Mário R. Pascoa; Myrian Petrassi; Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2008)
The uniform impatience hypothesis, a joint requirement on endowments and preferences, was imposed in the literature to prove equilibrium existence in infinite horizon sequential economies. In this note, we characterize this assumption in terms of asymptotic properties on inter-temporal discount factors.
Keywords: 330; Uniform impatience; inter-temporal discounting. JEL Codes: D50; D52.